CC and CXC chemokines in turbot (Scophthalmus maximus L.): Identification, evolutionary analyses, and expression profiling after Aeromonas salmonicida infection. Issue 127 (August 2022) - Fu, Qiang; Hu, Jie; Zhang, Pei; Li, Yuqing; Zhao, Shoucong; Cao, Min; Yang, Ning; Li, Chao
Abstract: Chemokines are a superfamily of structurally related cytokines, which exert essential roles in guiding cell migration in development, homeostasis, and immunity. CC and CXC chemokines are the two major subfamilies in teleost species. In this study, a total of seventeen CC and CXC chemokines, with inclusion of twelve CC and five CXC chemokines, were systematically identified from the turbot genome, making turbot the teleost harboring the least number of CC and CXC chemokines among all teleost species ever reported. Phylogeny, synteny, and genomic organization analyses were performed to annotate these genes, and multiple chemokine genes were identified in the turbot genome, due to the tandem duplications (CCL19 and CCL20), the whole genome duplications (CCL20, CCL25, and CXCL12), and the teleost-specific members (CCL34-36, CCL44, and CXCL18). In addition, chemokines were ubiquitously expressed in nine examined healthy tissues, with high expression levels observed in liver, gill, and spleen. Moreover, most chemokines were significantly differentially expressed in gill and spleen after Aeromonas salmonicida infection, and exhibited tissue-specific and time-dependent manner. Finally, protein-protein interaction network (PPI) analysis indicated that turbot chemokines interacted with a few immune-related genes such as interleukins, cathepsins, stats, and TLRs. These results should be valuable for comparative immunological studies and provide insights for further functional characterization of chemokines in teleost. Highlights: Twelve CCLs and five CXCLs were characterized in turbot genome. Gene duplications and teleost-specific members of chemokines were observed in turbot genome. Turbot chemokines were ubiquitously expressed, with high expression levels in liver, gill, and spleen. Most turbot chemokines were differentially expressed in spleen and gill after Aeromonas salmonicida infection.